A comment on Bauer, Lakdawala, Mueller: Market-Based Monetary Policy Uncertainty (2022) - Jaromir Baxa; Nino Buliskeria; Ali Elminejad; Tomas Havranek; Zuzana Havrankova; Suranjana Kundu (Institute for Replication (I4R), 2023)
Bauer et al. (2022) derive market-based monetary policy uncertainty and uncover an 'FOMC uncertainty cycle' characterized by a fall of uncertainty after FOMC announcements and its subsequent built-up. Then, the authors show that the financial markets' response to monetary policy announcements depends on the level of short-rate uncertainty on the day before the FOMC announcement. First, we reproduced the paper's findings, though with Matlab version-specific issues. Second, we tested the robustness of the two main results of the paper. We show that the uncertainty cycle in the monetary policy uncertainty is confirmed when the crisis period is included in the sample or when the median instead of the average of changes in the monetary policy uncertainty is considered. However, the FOMC uncertainty cycle does not appear when the monetary policy uncertainty index (Husted et al. 2020) or the daily economic policy uncertainty index (Baker et al. 2016) are used as uncertainty proxies.
Keywords: E43; E52; 330; Uncertainty; Monetary policy; Replication